1988
DOI: 10.1007/bf00177554
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of MAO-A, not MAO-B, results in antidepressant-like effects on DRL 72-s behavior

Abstract: The effects of monoamine oxidase inhibitors (MAOIs) that selectively inhibit the MAO-A or MAO-B forms of MAO were studied in rats performing under a differential-reinforcement-of-low-rate 72-s (DRL 72-s) schedule of reinforcement. Clorgyline and CGP11'305A, irreversible and reversible MAO-A inhibitors, respectively, increased the reinforcement rate, decreased the response rate, and enhanced temporal discrimination. The irreversible MAO-B inhibitor (-)-deprenyl did not produce similar effects. Pargyline did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…BIMT 17 shifted the PkL toward shorter IRT durations while imipramine shifted PkL toward longer IRT durations. Previous research (Seiden et al 1985;Marek and Seiden 1988a;Richard et al 1993b) has shown that a variety of antidepressant compounds shift the peak of the IRT distribution toward longer IRT durations without decreasing PkA. This shift in the IRT distribution toward longer waiting times results in an increased reinforcement rate.…”
Section: Drl 72-smentioning
confidence: 86%
“…BIMT 17 shifted the PkL toward shorter IRT durations while imipramine shifted PkL toward longer IRT durations. Previous research (Seiden et al 1985;Marek and Seiden 1988a;Richard et al 1993b) has shown that a variety of antidepressant compounds shift the peak of the IRT distribution toward longer IRT durations without decreasing PkA. This shift in the IRT distribution toward longer waiting times results in an increased reinforcement rate.…”
Section: Drl 72-smentioning
confidence: 86%
“…It has been claimed that the number of reinforcements earned by rats in the DRL 72 s schedule can be increased by the administration of compounds which have antidepressant e¤ects in man (ODonnell and Seiden 1983). This claim has been supported by a number of studies which have examined a wide variety of antidepressant treatments on DRL 72 s schedule behaviour, including 5-HTP (a 5-HT precursor with antidepressant e¦cacy; Marek et al 1989a), tricyclic antidepressants (McGuire and Seiden 1980a), monoamine oxidase inhibitors (ODonnell and Seiden 1982;Marek and Seiden 1988a), 5-HT reuptake inhibitors (Marek et al 1989a), 5-HT 2 antagonists (Marek et al 1989b) and electroconvulsive shock (Seiden et al 1985). In contrast, non-antidepressant treatments are reported to decrease the reinforcement rate on the DRL 72 s schedule (ODonnell and Seiden 1983).…”
Section: Introductionmentioning
confidence: 91%
“…Thus, monoamine oxidase inhibitors (O'Donnell and Seiden 1982;Marek and Seiden 1988a) and electroconvulsive shock (Seiden et al 1985) enhance efficiency both by an increase in reinforcement rates and a simultaneous decrease in response rates. Further, the "atypical" agents mirtazapine and mianserin, which possess 5-HT 2C and α 2 -adrenoceptor (AR) antagonist properties, similarly improve DRL 72-s performance by increasing reinforcement rates and/or decreasing response rates (O'Donnell and Seiden 1983;Marek et al 1989b;Hand et al 1991;Jackson et al 1995;Jones et al 1998).…”
Section: Introductionmentioning
confidence: 96%